2013
DOI: 10.1590/s0100-29452013000300016
|View full text |Cite
|
Sign up to set email alerts
|

Produção e qualidade físico-química de frutos de laranjeiras 'Valência' em diferentes intensidades e frequências de poda

Abstract: RESUMO -A poda de frutificação em citricultura pode ser aplicada com o objetivo de controlar o crescimento vegetativo e promover a formação de novos ramos frutíferos. Neste sentido, o objetivo deste trabalho foi avaliar diferentes regimes de poda manual em pomares jovens de Laranjeiras 'Valência', cultivadas em manejo convencional. Utilizou-se um pomar com espaçamento de 5,0 x 2,5 m, implantado em 2001 no município de Montenegro-RS, Brasil. Os tratamentos, com início em 2004, foram: A -Testemunha (sem poda); B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
1
0
0
Order By: Relevance
“…Considering the ideal standards for maturation of an orange fruit proposed by Azevêdo (2003) and CEAGESP (2011) Azevedo (2003) and CEAGESP (2011), ranging from 36 to 57%, which is similar values to those found in this paper. Santarosa et al (2013), in a study to assess the variation of intensity and frequency of pruning, found TM values similar to those found in our experiment, 280 g, especially in the control treatment (224 g). Table 2 shows an analysis of the spatial variability model with the parameters of the adjusted models to semivariograms.…”
Section: Discussionsupporting
confidence: 90%
“…Considering the ideal standards for maturation of an orange fruit proposed by Azevêdo (2003) and CEAGESP (2011) Azevedo (2003) and CEAGESP (2011), ranging from 36 to 57%, which is similar values to those found in this paper. Santarosa et al (2013), in a study to assess the variation of intensity and frequency of pruning, found TM values similar to those found in our experiment, 280 g, especially in the control treatment (224 g). Table 2 shows an analysis of the spatial variability model with the parameters of the adjusted models to semivariograms.…”
Section: Discussionsupporting
confidence: 90%
“…In mature trees, pruning intensity depends on the pruning type, frequency, and purpose (Table 2). When pruning is annual, it does not need to be intense [85]. The lower the frequency is, the more intense the pruning should be [5].…”
Section: Mature Treesmentioning
confidence: 99%
“…At the same time, enabling aeration and light penetration into the canopy is crucial. Maintenance pruning also improves nutrient distribution across branches [43,78,85,88].…”
Section: Maintenance or Fruiting Pruningmentioning
confidence: 99%